The influence of different ways of defining windows in computational models of residential buildings on their energy demand for heating - Kęskiewicz, Piotr (Instal, 2026)
This article presents an analysis of the impact of different methods and precision of defining window structures when creating a computational model of a single-family building on the obtained simulation results of the building’s central heating system’s energy consumption. Calculations were performed using the EDSL TAS simulation program, based on a typical Polish single-family building with minimum and recommended glazing areas. Ultimately, four different window structure definition methods were considered, including the introduction of: a fixed window frame width; a percentage of glazing to the total window area derived from the literature and determined based on the actual construction of the selected windows; and a faithful representation of the structural details of the selected windows. The results are presented globally for the analyzed building, individually for each room, and in detail for the room with the largest glazing area.
Keywords: energy consumption; energy simulations; calculation accuracy; model quality; share of glazing